Nature's keepers : the new science of nature management - Budiansky, Stephen (New York : Free Press, 1995)
Ecological science has begun to make sense of the baffling paradoxes of natural systems, finding the answers in a "mathematical ecology" - the mathematical relationships that link all creatures and plants in a natural community. This book introduces and examines this theory.
Includes bibliographical references
Keywords: Nature conservation; Nature -- Effect of human beings on; Philosophy of nature; Ecosystem management